2013
DOI: 10.1177/0148607113517716
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Cohort Study of the Outcome of and Risk Factors for Intravascular Catheter‐Related Bloodstream Infections in Children With Intestinal Failure

Abstract: The diagnosis of CRBSI should be questioned in the absence of fever and/or elevated CRP. Salvage of catheters should be attempted with all bacterial CRBSIs, assuming that the child is stable since the CVC can be retained in the majority of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
40
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 16 publications
7
40
3
Order By: Relevance
“…Therefore, the absence of fever and leukocytosis did not necessarily indicate an absence of infection. Elevation in CRP was a more sensitive indicator in our study, consistent with the findings from Robinson et al 40 However, CRP can take up to 24 hours after the onset of an infection to become elevated and has been suggested to have little utility in assisting in the early detection of sepsis 30 . In general, it has been used to serve as a surrogate marker of successful eradication of infection as the CRP level returns to normal with treatment of infection 41 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, the absence of fever and leukocytosis did not necessarily indicate an absence of infection. Elevation in CRP was a more sensitive indicator in our study, consistent with the findings from Robinson et al 40 However, CRP can take up to 24 hours after the onset of an infection to become elevated and has been suggested to have little utility in assisting in the early detection of sepsis 30 . In general, it has been used to serve as a surrogate marker of successful eradication of infection as the CRP level returns to normal with treatment of infection 41 .…”
Section: Discussionsupporting
confidence: 88%
“…In a recent prospective cohort study of 16 PIF patients receiving HPN, although the presence of fever and elevation of CRP were the most common indicators of sepsis, fever was not present in 12.5% of cases. The authors concluded that a diagnosis of CLABSI should be questioned in their absence 40 . We also found that patients with CLABSI presented more frequently with fevers, but 15% of patients did not have a fever at initial evaluation.…”
Section: Discussionmentioning
confidence: 52%
“…Notably, prospective studies are more likely to accurately capture all CRBSI episodes compared with retrospective studies, which may miss positive blood cultures sent at referring outside hospitals or emergency rooms. While our overall CRBSI rate of 3.6 per 1000 catheter days is relatively high, it is consistent with the CRBSI rate of 4.6 per 1000 catheter days described in a separate prospective study of Canadian pediatric home PN patients . These rates suggest that CRBSIs may be more common in the pediatric compared with the adult home PN population.…”
Section: Discussionsupporting
confidence: 88%
“…CRBSIs are known to be the most common and serious complication for patients receiving home PN. The varying rates of CRBSIs reported in the literature are likely due to differences in study design and heterogeneous patient cohorts . Notably, prospective studies are more likely to accurately capture all CRBSI episodes compared with retrospective studies, which may miss positive blood cultures sent at referring outside hospitals or emergency rooms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation